ASSESSMENT OF ATTRITION IN PATIENTS WITH DEEP BITE - A UNIVERSITY HOSPITAL BASED STUDY - Manohar, Janhvi; Srirengalakshmi; S.P. , Saravana Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Deep bite malocclusion is described as the overlap of upper incisors on the labial surface of lower incisors vertically when the standard limit of 1 to 2 millimeters is exceeded. Correction of deep bite is crucial for maintenance of dental hard and soft tissue structures and for prevention of temporomandibular joint disorders. Untreated deep bite over a prolonged duration results in attrition of the lingual surfaces of the mandibular incisors or anteriors. Grippo defined attrition as the loss of dental hard tissue as a result of tooth-to-tooth friction without any additional factors. Furthermore, presence of worn dentition decreased bony support, temporomandibular joint dysfunction poses challenges in the orthodontic treatment of adults. The problem of the correction of a deep overbite, even though complicated, resolves many future complications. The aim of this study is to evaluate the prevalence and association of attrition in patients having a deep overbite. Records were obtained from an outpatient department record of a private dental college, and a retrospective analysis was done among 513 patients with deep bite among which 293 were males and 219 were females and one of them identified as a transgender. Data was collected, tabulated and correlation tests were performed. Out of 513 patients with deep overbite, 239 patients were observed as having attrition. Higher prevalence of attrition in deep overbite was observed in males. Patients with deep bite within the age group 31-50 years were more commonly observed with attrition.